Pengembangan Aplikasi Penyewaan Lapangan Futsal di Tiki-Taka Barcelona Futsal Berbasis Android dan Web - Nur Rohman, Aziz; Fachrie, Muhammad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Tiki-taka Barcelona Futsal is one of the places to rent futsal fields in Prambanan. The data collection and rental system at Tiki-taka Barcelona Futsal is still classified as manual, where renters must first ask for empty schedules via the WhatsApp application or come directly. This manual system has an impact on tenants and groundskeepers. Renters have to WhatsApp or come directly to the place which takes quite a long time because the guards or field admins are not always online on WhatsApp and the guards or field admins have to answer one by one if many people ask questions and not all renters have to travel distance to Tiki-taka Barcelona Futsal. near. By creating an Android and web-based futsal field rental application, it can make it easier for tenants to rent the field and for keepers to manage the field. This application can also carry out online transactions using Midtrans.